Pengaruh Persepsi Perilaku Narsistik dalam Kelompok terhadap Pengambilan Keputusan Etis Mahasiswa Manajemen Universitas Muhammadiyah Bandung - Almaira Sarah Junjunan; Nisa Febrianti; Sarah Mutia Azahra; Sofa Parihah Nurasiah (Indo Publishing, 2026)
This study aims to examine the effect of students' perceptions of narcissistic behavior in academic groups (X) on their ethical decision-making (Y). A quantitative survey design was employed. Data were collected from 35 active students of the Management Study Program at Universitas Muhammadiyah Bandung using convenience sampling through an online questionnaire consisting of 20 Likert-scale items. The instrument testing indicated that all items were valid (item-total correlation ranging from 0.355 to 0.843) and reliable (Cronbach's Alpha = 0.943 for variable X and 0.824 for variable Y). Descriptive statistics showed relatively high mean scores for both perceptions of narcissistic behavior (mean = 4.01) and ethical decision-making (mean = 4.11). Simple linear regression analysis produced the equation Y = 3.415 + 0.173X, with R² = 0.080 and p = 0.101, indicating that perceptions of narcissistic behavior did not have a statistically significant effect on ethical decision-making. Interestingly, the observed relationship was positive, contrary to the initial hypothesis. These findings suggest that the research instrument is more likely to capture respondents' evaluations of the negative impact of narcissistic behavior within groups rather than the actual extent to which they experience narcissistic behavior in their group interactions.